Effects of Extruded Soy Protein on the Quality of Chinese Steamed Bread - Zhenya Du; Fusheng Chen; Kunlun Liu; Shaojuan Lai; Lifen Zhang; Guanhao Bu; Xueli Gao; Shaobo Liu (Journal of Chemistry)
Five different extruded soy protein isolates (ESPIs) were obtained by extrusion and denoted by IVD1, IVD2, IVD3, IVD4, and IVD5. Then the SDS-PAGE results showed that the subunits of SPI decreased after extrusion, especially the subunits of 90.8, 32.8, and 31.3 kDa, whereas no isopeptide bond was formed. Although SPI improved both the development time (DT) and stability (S) of dough, ESPIs increased S but the DT decreased from 4.3 min to 1.8–2.0 min. Texture profile analysis (TPA) results showed that the hardness and chewiness of Chinese steamed bread (CSB) decreased in the order wheat flour+IVD2 (WF+IVD2), WF+SPI, WF+IVD4, WF+IVD1, WF+IVD3, WF, and WF+IVD5. As regards color, the total color ΔE decreased except for the WF+IVD1 (56.22); its positive and negative trends of L⁎ and b⁎ were invariant with the SPI or ESPIs mixture, whereas a⁎ showed a positive trend. The sensory score increased from 82.7 to 83.4 with 3% of SPI addition and up to 87.8 when the substitution was IVD1. Therefore, SPI treated by extrusion may significantly improve the quality of CSB.